All-optical observation and reconstruction of spin wave dispersion - Yusuke Hashimoto (Nature Portfolio, 2017)
Observation of the entire dispersion relation for spin waves remains a challenge which prevents the full understanding of many intriguing magnetic properties. Here, the authors develop a table-top all-optical approach to map out the dispersion curve of pure-magnetostatic waves in magnetic films.